(untitled) (Research, Society and Development, 2021)
The present research brought as a theme: “Mistress’s Rigth: the legal effects of concubinary relations”, having as guiding question: what are the mistress’s right in the face of a still-established marriage? The general objective of the study was to analyze the rights that may be granted to mistress in the legal sphere in relation to the current doctrinal or jurisprudential positioning. And as specific objectives, it aimed to present concepts and characteristics of the family today, to identify matrimonial duties and their legal repercussions, and to seeking to differentiate concubinagem from plurid relationships. For this purpose, bibliographic research was used as methodology, having as source books, current legislation, legal journals, consultation on websites specialized in Law, in addition to scientific articles published in available database, such as Scielo and Google Academic. This study is justified by its great relevance of the current society, dealing with common situations that have always existed in all the developments of the history of humanity, itself, although it still remains under a moral perspective and prejudiced, due to the duty of fidelity still enshrined in the legal system, to be a Strong pillar of monogamous society. At the end, it was concluded that the mistress came out of limbo, currently reaching the Judiciary innumerable demands made by people involved in this type of extramarital relationship. It can be observed that, although the prejudiced view that links mistress is still stagnant, they are no longer silent before third parties, emphasizing that, in the current scenario, they are not conferred family rights to the lovers themselves, and only the existence of rights consistent with the obligatory nature can be verified.